1977
DOI: 10.1111/j.1365-2125.1977.tb00786.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on the response to anticoagulants.

Abstract: 1 A group of 114 patients on long‐term anticoagulant therapy was studied. The daily maintenance dose of both phenprocoumon, bishydroxycoumarin and warfarin was found to be significantly lower in patients aged between 61 and 70 years than in the those between 50 and 60 years of age. The mean daily dose of bishydroxycoumarin, hower, when expressed on a weight basis, was not significantly lower in the elderly. 2 For bishydroxycoumarin but not for phenprocoumon and warfarin there was found a statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Husted & Andreasen (1977) found that a therapeutic dose of bishydroxycoumarin could be correlated to the bodyweight of the patient but that such a correlation could not be found for either phenprocoumon or warfarin.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Husted & Andreasen (1977) found that a therapeutic dose of bishydroxycoumarin could be correlated to the bodyweight of the patient but that such a correlation could not be found for either phenprocoumon or warfarin.…”
Section: Methodsmentioning
confidence: 98%
“…It can be seen that a statistically significant negative correlation between mean tablet dose and age was found for the whole group, and for both males and females when analysed separately. Husted & Andreasen (1977) have reported greater sensitivity for warfarin with increasing age and in addition they also found a connection between age and dose for bishydroxycoumarin. This study was however not controlled and the patient material was inhomogenous.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acenocoumarol daily dose expressed in mg/kg fell with increasing age, this decrease being most pronounced from the third to the fifth decade (see Table 5). Variations in the degree Husted & Andreasen (1977) found that the daily maintenance dose of both phenprocoumon, bishydroxycoumarin and warfarin in 114 patients on long-term anticoagulant therapy was significantly lower in patients aged between 61 and 70 years than in those between 50 and 60 years. However, when expressed on a weight basis, the mean daily dose of bishydroxycoumarin was not significantly lower in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…For some of them, for example age, the direction and the degree with which they interfere with the effects of oral anticoagulants has been determined with some precision (O'Malley et al, 1977;Husted & Andreasen, 1977;Shepherd et al, 1977;Routledge et al, 1979). Other factors such as sex and indication for treatment remain controversial and uncertain (O'Malley et al, 1977;Routledge et al, 1979;Arboix et al, 1984).…”
Section: Discussionmentioning
confidence: 99%